Reintroducing Pitirim A. Sorokin - Nichols, Lawrence T., author. aut Link Link Link
1 online resource.
Keywords: "Reintroducing Pitirim A. Sorokin acquaints readers with the work and creativity of one of sociology's greatest scholars, highlighting the enduring importance of his thought and vision. Forced to leave his native Russia by war and revolution, Sorokin (1889-1968) had a profound effect on sociology in the US, where he helped to found several mainstream subfields of sociology and developed the discipline in new directions, including with his philosophy Integralism. Exploring Sorokin's research on culture, civilizational change and the sociology of love, as well as his advocacy of a peaceful international order blending the cultures of East and West, this book highlights Sorokin's contribution to sociology, demonstrating that his work anticipates many of the problems of our new millennium and considering the ways in which his ideas continue to challenge and inspire us, while offering routes to addressing the difficulties we face. The book will appeal to scholars across the social sciences with interests in social theory and the history of sociology, as well as in the sociology of culture, the sociology of war and peace, and the sociology of morality and altruism"-- Provided by publisher.